2011
DOI: 10.1111/j.1460-9568.2011.07763.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of P2X4 receptors in synaptic strengthening in mouse CA1 hippocampal neurons

Abstract: P2X4 receptors are calcium-permeable cation channels gated by extracellular ATP. They are found close to subsynaptic sites on hippocampal CA1 neurons. We compared features of synaptic strengthening between wild-type and P2X4 knockout mice (21–26 days old). Potentiation evoked by a tetanic presynaptic stimulus (100 Hz, 1 s) paired with postsynaptic depolarization was less in P2X4−/− mice than in wild-type mice (230 vs. 50% potentiation). Paired-pulse ratios and the amplitude and frequency of spontaneous excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 35 publications
(75 reference statements)
3
52
0
Order By: Relevance
“…Of the seven P2X subunits characterized to date (named P2 Â 1 through P2 Â 7), P2X4 receptors (P2X4Rs) are the most abundant in the central nervous system (Buell et al, 1996;Soto et al, 1996), and are expressed in neurons across multiple regions of the brain and spinal cord, as well as in microglia (Burnstock and Knight, 2004;Ulmann et al, 2008). Recent studies have pointed to the implication of P2X4 in the regulation of multiple nervous functions, including neuropathic pain (Tsuda et al, 2003;Ulmann et al, 2008), neuroendocrine functions (Zemkova et al, 2010), and hippocampal plasticity (Baxter et al, 2011;Lorca et al, 2011;Sim et al, 2006). In addition, P2X4 receptors have been recently shown to modulate the function of other major ionotropic targets, such as N-methyl-D-aspartate (NMDA) glutamate receptors (Baxter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the seven P2X subunits characterized to date (named P2 Â 1 through P2 Â 7), P2X4 receptors (P2X4Rs) are the most abundant in the central nervous system (Buell et al, 1996;Soto et al, 1996), and are expressed in neurons across multiple regions of the brain and spinal cord, as well as in microglia (Burnstock and Knight, 2004;Ulmann et al, 2008). Recent studies have pointed to the implication of P2X4 in the regulation of multiple nervous functions, including neuropathic pain (Tsuda et al, 2003;Ulmann et al, 2008), neuroendocrine functions (Zemkova et al, 2010), and hippocampal plasticity (Baxter et al, 2011;Lorca et al, 2011;Sim et al, 2006). In addition, P2X4 receptors have been recently shown to modulate the function of other major ionotropic targets, such as N-methyl-D-aspartate (NMDA) glutamate receptors (Baxter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have pointed to the implication of P2X4 in the regulation of multiple nervous functions, including neuropathic pain (Tsuda et al, 2003;Ulmann et al, 2008), neuroendocrine functions (Zemkova et al, 2010), and hippocampal plasticity (Baxter et al, 2011;Lorca et al, 2011;Sim et al, 2006). In addition, P2X4 receptors have been recently shown to modulate the function of other major ionotropic targets, such as N-methyl-D-aspartate (NMDA) glutamate receptors (Baxter et al, 2011). These ion channels have been implicated in the organization of emotional and cognitive responses (Newcomer and Krystal, 2001), as well as in the pathophysiology of neurodevelopmental conditions, such as autism-spectrum disorder (ASD) (Carlson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An example of the involvement of ATP in neuromodulation is given by the observation made by diverse groups at the beginning of the present millennium, when using pharmacological and genetic approaches was possible to establish the involvement of P2X receptors in the formation of LTP in rat hippocampus [46][47][48]; for instance, in P2X4-KO mice was detected an impairment in LTP formation in hippocampus [49,50], this modification could be due to a reduction in synaptic [Ca 2+ ] [50] and related to that, a lower incorporation of NR2B subunits at the post-synapse [49]. Another interesting aspect to P2X receptors is the capability of interact with other types of receptors, such as nicotinic ␣4␤2 which interacts with P2X2 [41], this provokes a cross-inhibition of both.…”
Section: P2x Receptors and Synaptic Regulationmentioning
confidence: 98%
“…However, Ca 2+ entry via P2X receptors may cause modulation of NMDA receptor function, for example by calcium-dependent inactivation [251]. Further, Baxter et al [252] reported that the absence of P2X4 receptors limited the incorporation of GluN2B subunits into synaptic NMDA receptors in mouse hippocampus.…”
Section: Purinergic Modulation Of Glutamatergic Neurotransmissionmentioning
confidence: 99%